Estimating the Underreporting Rate of Injured Cyclists - Pauer, Gábor; Krizsik, Nóra; Szigeti, Szilárd (Periodica Polytechnica Civil Engineering, 2023)
International data reports indicated that underreporting is a frequent phenomenon in the case of cyclist accidents. However, determining the exact volume of underreported accidents or injured cyclists is a difficult task. Our research focused on a comprehensive examination of the personal injury accident data of cyclists. The primary aim was to elaborate a model determining the proportion of injured cyclists ‘missing’ from the official accident database and to explore the possible causes and processes leading to that. With the use of various data sets (accident database, data from hospitals and survey of cyclists), the model can alleviate the distortion effects arising from conclusions reached using only one data source. To demonstrate applicability, the surveys and examinations were carried out in relation to Hungary. The results showed that only 8.3% of injured cyclists were reported in the official accident database. The majority (62.6%) of injured cyclists received neither police action, nor medical treatment. The volume of the underreporting varied depending on the injury outcome and type of accident.